News Commentaries April 1960 - Abrahams, Peter (My University, 1960)
News commentaries broadcast in April of 1960. List of subjects included at the beginning
53 pgs. Typescript, letter-sized, sepia-toned, in fairly good condition.
Keywords: Abrahams, Peter, 1919 – 2017; News commentaries – Jamaica; Politics – Jamaica; Nuclear energy; Constitutional amendments – British Guiana; Constitutions – British Guiana; Leave of absence – Jamaica; Taxation; Jones, Absolom; Strikes and lockouts – Jamaica; Riots – South Korea